Empowering the Creative Economy Through CBSE: Ecotourism and Revitalizing Local Village Wisdom - Dedi Hariyanto; Fita Kurniasari; Pratika Linanda; Mahardika Agung Madepo (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Sungai Deras Village has untapped ecotourism and local wisdom potential. This community service program aims to empower the creative economy through a Community-Based Social Enterprise approach, focusing on developing community-based ecotourism and revitalizing local wisdom. The community service partners are the Sungai Deras Village Tourism Awareness Group and Family Welfare Movement (PKK), which face challenges in management capacity, product innovation, supporting infrastructure, marketing, local wisdom integration, and sustainable business models. The implementation method uses a participatory approach with stages of outreach, training, mentoring, program implementation, and evaluation. Activities include strengthening human resource capacity, developing innovative tourism products, improving infrastructure, digital marketing training, standardizing local wisdom products, and developing a social enterprise business model. The results of the community service program demonstrate increased partner capacity in ecotourism management and developing local wisdom products, creating synergy between the tourism and creative economy sectors, and establishing a sustainable business model that integrates economic, social, and environmental aspects. This program has successfully increased community income, strengthened local cultural identity, and encouraged environmental conservation. The empowerment model developed can be a reference for implementing Community Based Social Enterprise for villages with similar characteristics in optimizing ecotourism potential and local wisdom.